Associations between occupation and heavy alcohol consumption in UK adults aged 40-69 years: a cross-sectional study using the UK Biobank - Andrew Thompson; Munir Pirmohamed (BMC, 2021)
Abstract Background Understanding the relationship between occupation and alcohol use offers opportunities to provide health promotion programmes based on evidence of need. We aimed to determine associations between occupation and heavy alcohol consumption in working individuals aged 40-69 years. Methods A cross-sectional study was conducted using 100,817 people from the UK Biobank: 17,907 participants categorised as heavy drinkers, defined as > 35 units/week for women and > 50 units/week for men, and 82,910 drinking controls. Prevalence ratios (PRs) and 95% CIs were calculated for gender-specific heavy drinking in 353 occupations using Standard Occupational Classification, V.2000. Results Seventy-seven occupations were associated with level of alcohol consumption in drinkers. The largest ratios for heavy drinkers were observed for publicans and managers of licenced premises (PR = 2.81, 95%CI 2.52-3.14); industrial cleaning process occupations (PR = 2.09, 1.33-3.28); and plasterers (PR = 2.07, 1.66-2.59). Clergy (PR = 0.20, 0.13-0.32); physicists, geologists and meteorologists (PR = 0.40, 0.25-0.65); and medical practitioners (PR = 0.40, 0.32-0.50) were least likely to be heavy drinkers. There was evidence of gender-specific outcomes with the proportion of jobs associated with heavy drinking accounted for by skilled trade occupations being 0.44 for males and 0.05 for females, and 0.10 for males and 0.40 for females when considering managers and senior officials. Conclusions In the largest study of its kind, we found evidence for associations between a wider variety of occupations and the risk of heavy alcohol consumption than identified previously, particularly in females, although causality cannot be assumed. These results help determine which jobs and broader employment sectors may benefit most from prevention programmes.